Penerapan Struktur Penceritaan pada Film Dua Garis Biru Berdasarkan Pendekatan Sequence - Angga Setyo Apriyono; Sri Wastiwi Setiawati (Texture:Art and Culture Journal, 2022)
This study aims to describe the application of the story structure in the film Dua Garis Biru based on Paul Joseph Gulino’s sequence approach. The research method used is qualitative research. The results showed that  the  structure  of  the  story  used  in  the  film  Dua  Garis  Biru  uses  an  eight-sequence  story  structure approach. Sequence 1 begins with the introduction of the main characters Dara and Bima with their lives, and  there  is  a  point  of  attack  when  it  is  confirmed  that  Dara  is  pregnant  due  to  having  sex  with  Bima. Sequence 2 introduces the limitations of Dara and Bima which affect the way they will run to overcome the problem by covering up Dara’s pregnancy. Sequence 3 Bima and Dara began to carry out their plan but an unexpected obstacle appeared that made Dara’s pregnancy revealed which resulted in Dara having to be expelled from school and expelled from the house. Sequence 4 shows how poorly prepared the characters are and the midpoint culmination appears. Sequence 5 shows the consequences of the midpoint culmination which  makes  Bima  finally  married  to  Dara,  although  a  bigger  problem  arises.  Sequence  6  shows  the consequences of a big problem at the end of sequence 5 leading Dara to realize that they have not been able to become parents, which makes Dara and Bima do the last resort which is risky. At the beginning of sequence 7 an unexpected problem arose from Dara and Bima’s final plan, which made them aware of the importance of the role of parents in children’s growth, then led to a twist, namely Bima finally chose to take care of his own child. Sequence 8 problems were finally resolved, Bima took care of his son and Dara went to Korea.